1990
DOI: 10.1021/bi00495a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of extended and deleted recombinant analogs of parathyroid hormone-(1-84): correlation of peptide structure with function

Abstract: Recombinant analogues of human parathyroid hormone [hPTH-(1-84)] were expressed in Escherichia coli harboring plasmids containing synthetic genes under the control of the lac promoter. The level of expression of the gene encoding the truncated analogue, hPTH-(3-84), was greater than that of the gene encoding full-length hPTH-(1-84) but less than that of the gene encoding proparathyroid hormone (hProPTH). This may be due in part to the relative efficiency of translation of the mRNA as suggested by secondary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In fact, deletion of the first two amino acids leads to a peptide that binds to the receptor but is almost devoid of biological activity (6). Studies based on hydrophilicity plots and on the characteristics of most antibodies produced against the amino-terminal segment of the molecule showed that the dominant epitope of this section of the PTH molecule is located in the region between amino acids 15 and 26 (7).…”
mentioning
confidence: 99%
“…In fact, deletion of the first two amino acids leads to a peptide that binds to the receptor but is almost devoid of biological activity (6). Studies based on hydrophilicity plots and on the characteristics of most antibodies produced against the amino-terminal segment of the molecule showed that the dominant epitope of this section of the PTH molecule is located in the region between amino acids 15 and 26 (7).…”
mentioning
confidence: 99%
“…This regulation is remarkable given that PTH (an 84-amino acid peptide) and PTHRP (a 139 -173-amino acid peptide depending on the species) (10) share minimal identity in primary structure, with only 8 of the 13 N-terminal amino acids being common between these two peptides. PTH and PTHRP require the first two N-terminal amino acids and amino acids 25-34 to stimulate adenylate cyclase activity (11)(12)(13)(14). In contrast, amino acids 3-34 and even smaller regions (amino acids 28 -34) appear sufficient to activate PKC translocation to the plasma membrane (15)(16)(17).…”
mentioning
confidence: 99%
“…Direct expression in E. coli delivers only very small amounts of hPTH (see Table 2; Breyel et al 1984;Rabbani et al 1988Rabbani et al , 1990Hagset et al 1990). The construction of a gene fusion allowed synthesis of a stable hybrid protein to higher concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 summarizes previous studies on the expression of h P T H and some derivatives using various host/vector systems. Usually, the h P T H concentration achievable is low, i.e., 0.2-3 mg/1 (Breyel et al 1984;Rabbani et al 1988Rabbani et al , 1990Hogset et al 1990). Higher expression can obviously be obtained for N-terminal elongated derivatives of h P T H (Wingender et al 1989;Rabbani et al 1990).…”
Section: Fed-batch Operationmentioning
confidence: 99%
See 1 more Smart Citation